2016
DOI: 10.1158/1078-0432.ccr-15-1681
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of the Safety, Pharmacokinetics, and Pharmacodynamics of Combination Therapy with Refametinib plus Sorafenib in Patients with Advanced Cancer

Abstract: Purpose: To assess the safety and tolerability of the smallmolecule allosteric MEK inhibitor refametinib combined with sorafenib, in patients with advanced solid malignancies.Experimental Design: This phase I dose-escalation study included an expansion phase at the maximum tolerated dose (MTD). Patients received refametinib/sorafenib twice daily for 28 days, from a dose of refametinib 5 mg plus sorafenib 200 mg to a dose of refametinib 50 mg plus sorafenib 400 mg. Plasma levels of refametinib, refametinib meta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…RAS-MAPK signaling has been implicated in tumor progression and dissemination in HCC (2). A phase I study of the combination of refametinib with sorafenib in patients with advanced malignancies including HCC demonstrated a favorable safety profile and pharmacokinetic profile at a maximum tolerated dose of refametinib 50 mg twice daily in combination with sorafenib 400 mg twice daily (12).…”
Section: Introductionmentioning
confidence: 99%
“…RAS-MAPK signaling has been implicated in tumor progression and dissemination in HCC (2). A phase I study of the combination of refametinib with sorafenib in patients with advanced malignancies including HCC demonstrated a favorable safety profile and pharmacokinetic profile at a maximum tolerated dose of refametinib 50 mg twice daily in combination with sorafenib 400 mg twice daily (12).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to inhibit MAPK signalling downstream from MEK in vitro . Refametinib has been previously tested both alone [ 35 ] and in combination with both the mutli-target tyrosine kinase inhibitor sorafenib [ 36 ] and the PI3K inhibitor copanlisib [ 37 ] in Phase I and Phase II studies. It was well tolerated in all trials, with manageable drug-related adverse effects, either used alone or in combination with targeted therapies and demonstrated benefit in some patients with advanced cancer [ 35 - 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacodynamics analysis of patients recruited to the Phase I trial of refametinib [ 36 ] identified that refametinib can achieve a peak plasma conc of 700μg/ml (1.223μM). We classified HCC1954 cells which have an IC 50 of <500nM as sensitive to refametinib, whilst BT474 cells which have an IC 50 of 1.2μM are classified as slightly sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…No results appear to have been posted as of December 2019. A phase I safety study was performed on combining refametinib and sorafenib and demonstrated acceptable safety profiles [90]. Therefore, a phase II clinical trial (NCT01204177) to examine the effects of combining the drugs refametinib and sorafenib was performed with HCC patients [91].…”
Section: Background and Strategies Based On Targeting Ras/raf/mek/erkmentioning
confidence: 99%